Sistem Start Direct Online Motor Induksi 3 Phase Berbasis Internet of Things - Tarigan, Enda Rasilta; Rahmansyah, Abdul Azis; Gultom, Golfrid; Ginting, Manan (JOURNAL OF ELECTRICAL AND SYSTEM CONTROL ENGINEERING, 2024)
Digital technology continues to develop until now such as in Industry 4.0. In the industry, many still use conventional systems such as Induction Motor Starters using the Direct on Line (DOL) System. This study aims to build a system to be able to upgrade conventional systems to digital-based systems. The method used is testing by making a design and then comparing the data obtained to see the response time. From the results of the study, the system can work well. Both testing on conventional systems and online systems. In conventional systems, the system works faster with an average response time of less than 1 second, while with an online system, the response depends on the internet network used so that an average of 1.6 seconds is obtained. In addition, the results of testing using internet of things software show that the system is integrated between conventional systems and digital systems where when the induction motor is ON, a current reading of around 60A will be obtained on the IoT software display and when the motor is OFF, the current reading will drop to close to 0 Ampere.